Automating PrepFiler® forensic DNA extraction kit: Optimization and validation on Freedom EVO® 150. (December 2015) - Kallupurackal, V.; Kausel, T.; Sulzer, A.; Voegeli, P.; Kratzer, A.
Abstract: To handle the growing number of forensic casework samples we decided to automate our trace sample workflow using PrepFiler ® a magnetic bead based DNA extraction kit, on a Tecan liquid handling workstation Freedom EVO ® 150. Even though there was a manufacturer-supplied validated protocol for the automated PrepFiler ® DNA extraction, substantial changes were needed in order to obtain the optimal DNA yield and elution volume to meet the needs of our laboratory for further downstream applications. In this study, optimal lysis condition, elution volume and elution temperature were determined for the automated PrepFiler ® extraction using blood samples on cotton swabs. Additionally, a comparison with the manual in-house method Chelex-100 ® was made using a variety of forensic mock samples on swabs. We tested blood, saliva and contact traces from a variety of substrates, with 10 replicates of each type. With the automated PrepFiler ® system, the DNA yield obtained was around 30–70% lower than with Chelex-100 ® . However, the purity of the extracts was higher. Allele recovery of the STR profiles obtained with AmpFlSTR ® NGM SElect™ kit was comparable. Furthermore we found that, besides the kit-specific optimization factors, swab characteristics are of major importance for the success of PrepFiler ® DNA extraction. We incorporated the optimized PrepFiler ® protocol on Freedom EVO ® 150 into our routine workflow and included quality controls to maintain contamination-free and efficient DNA extraction with no evidence for loss of magnetic beads.